Employing recent technologies for improved digital governance - Ponnusamy, Vasaki 1974; Rafique, Khalid 1973; Zaman, Noor 1972 (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2020)
"This book explores recent advances in the development, application, and impact of technologies in digital governance"